Simultaneous Quantitative Analysis of Ephedrine HCl, Guaifenesin, and Some Synthetic Additives in Syrups by RP-HPLC Using Box-Behnken Design - Aksu Donmez, Ozlem; Asci, Burge; Dinc-Zor, Sule; Aslan Cakir, Ayse (COLEGIO FARMACEUTICOS PROVINCIA DE BUENOS AIRES, 2018)
In this paper, an accurate, precise and rapid HPLC method was developed for the simultaneous analysis of ephedrine HCl, guaifenesin and synthetic additives, including methylparaben, propylparaben, Ponceau 4R and saccharin in syrup samples. Optimum conditions of HPLC method were determined with the aid of Box-Behnken experimental design. The optimum separation of all analytes was achieved with phosphate buffer including 0.15% TBAH, pH 6.5, methanol gradient that follows 0-8.5 min, 52:48 (v/v); 8.5-20 min, 40:60 (v/v), with a flow rate of 0.6 mL/min. Under these conditions, the elaborated method was validated for linearity, limits of detection and quantification, precision and accuracy according to ICH guidelines. Afterwards, the proposed method was applied to commercial syrup samples and it can be said that this analytical method can be used for routine quality control determination of these components in syrup formulations, thereby saving time, effort and chemicals.
Keywords: Box- Behnken design; ephedrine HCl; guaifenesin; RP-HPLC; synthetic additive; PERFORMANCE LIQUID-CHROMATOGRAPHY; DIFFERENTIAL-PULSE POLAROGRAPHY; THIN-LAYER-CHROMATOGRAPHY; 2 MULTICOMPONENT MIXTURES; SODIUM BENZOATE; PHARMACEUTICAL-PREPARATIONS; SOFT DRINKS; PONCEAU 4R; ALLURA RED; METHYLPARABEN; Pharmacology & Pharmacy